Characteristics of cytomegalovirus enterocolitis in patients with or without inflammatory bowel diseases. (3rd April 2018) - Kang, Eun Ae; Yoon, Hyuk; Seo, A. Young; Shin, Cheol Min; Im, Jong Pil; Park, Young Soo; Kim, Joo Sung; Kim, Nayoung; Lee, Dong Ho
Abstract: Objectives: Cytomegalovirus (CMV) disease is more common in immunocompromised patients but may occur in people with normal immune function. In addition, CMV enterocolitis can aggravate inflammatory bowel diseases (IBD), but there was little knowledge of differences in clinical and endoscopic features of CMV enterocolitis between patients with IBD and without IBD. The aim of this study was to determine the difference in clinical implication in CMV enterocolitis between the IBD patients and non-IBD patients. Methods: This was a retrospective study of 82 patients with CMV enterocolitis based on the pathologic findings at two tertiary referral hospitals from 2003 to 2013. Clinical and endoscopic characteristics and clinical course were analyzed according to the presence of IBD. Results: Of the 82 patients, 25 (30.5%) had IBD and 57 (69.5%) did not have IBD. Hematochezia was more common in IBD patients (84.0% vs. 35.1%; p = .001), but fever and positive CMV antigenemia were more common in non-IBD patients (50.9% vs. 12.0%; p = .001; 54.4% vs. 28.0; p = .027). Endoscopic findings showed more ulcer with inflammation in IBD patients (68.0% vs. 35.2%; p = .005). Sixty-four patients were treated with antiviral agents and 12 patients who did not receive antiviral agents recovered spontaneously. All naturally healed patients were in normal immune status. Conclusions: Hematochezia is more common in IBD patients and fever/CMV antigenemia is more common in patients without IBD. In patients without IBD, the natural resolution of CMV enterocolitis is expected at least in normal immune function.